Environmental Management Through the Implementation of the Waste-sorting Program in Desa Kurungkambing - Maman Rumanta; Siti Hadianti; Hidayah Hidayah; Teguh Prakoso; Dewi Elfriwaty Br Simamora; Siti Nurlina (Universitas 45 Surabaya, 2025)
Environmental management through implementation of a waste sorting program in Desa Kurungkambing aims to raise public awareness of environmental issues and improve environmental conditions by applying the Reduce, Reuse, and Recycle (3R) concept. The methods employed in this program include ecological awareness training for the community, enhancement of waste-sorting infrastructure, and the development of a more efficient waste-sorting system. In this activity, the Community Service (PkM) team from Universitas Terbuka conducts training sessions to enhance the community’s understanding of the 3R concept while also improving infrastructure related to waste sorting. The implementation stages of this program include preparation, execution, evaluation, documentation, and dissemination. The outcomes of this PkM activity include a cleaner environment in Desa Kurungkambing, increased awareness and active participation of the community in waste sorting, and the establishment of Desa Kurungkambing as a positive example for neighboring villages.